Optimization of multi-channel quartz crystal microbalance for Gas Sensing Application - Zainuddin, Ahmad Anwar; Bhattacharjee, Soumik; Md Ralib, Aliza Aini; Mohd Sukri, Nurain Sufi Sabreena; Binti Kamarudin, Saidatul Izyanie; Subramaniam, Krishnan; Handayani, Dini Oktarina Dwi; Reyasudin Basir Khan, M.; Nik Mohd. Kamal, Nik Nor Muhammad Saifudin (IEEE, 2023)
Mass detection sensor Quartz Crystal Microbalance (QCM) measures mass sensitivity by piezoelectric, high frequency shaving on nanograms. These sensors detect with high precise geometry, low cost and ease of production. Conventional QCM sensors are limited to one electrode structure that minimizes the range of sensing. On a single quartz crystal substrate, three new QCM Multi-Channel sensors are developed and optimized that include 2-channel, 3- channel and 4-channel QCM sensors. The COMSOL Multiphysics software is used to design and simulate the multichannel sensors to enhance the device structure for applications with less interference frequency. From the results, it shows that the least interferences exhibit frequency values of 9.58MHz as both QCMs for the 5mm centre-to-centre (c2c). However, due to small c2c distances that decrease accuracy and operating disadvantages, this design was not selected. For 3 channel sensors, however, three resonant peaks show a similar value of 9.58MHz when c2c is maintained at 7mm. With the highest c2c distance this design shows less interference. Finally, for 4- channel sensors, a distance of 6 mm c2c also has a minimum interference with a 9.58 MHz resonance frequency. This shows that 4 channel sensors with the highest c2c can provide greater operational convenience and less interference at frequencies and thus maximize measurement accuracy. Multi-sensor arrays are advantageous when detecting a large number of analytes at the same time or when only selective coatings (coatings that respond to more than one analyte at the same time) are available. These sensor arrays, which use only one sensor and combine it with enhanced signal evaluation methods or prior sample separation to achieve the results of multi-sensor arrays, are becoming increasingly popular.